Environmental data and indicators and human security related issues in Romania: an institutional approach - Daniela Luminita Constantin (European Regional Science Association (ERSA), 2001)
When the environmental issues are addressed in sustainability, human security terms the information demand is getting more complex, emphasising the need to integrate environmental, economic and socio-cultural information. This paper proposes an insight into the data and indicator issues on environment and human security in Romania from an institutional perspective. To a country in transition like Romania creating appropriate organisational structures and legislation has beed a prerequisite to building a realistic and effective environmental protection strategy. Therefore a presentation of the institutional and legislative framework of environmental protection created after 1989, in comparison with the situation in the communist period, has been considered necessary for understanding the institutional context of environmental data collecting, transmitting, processing and employing. On this basis the environmental information system has been critically assessed in terms of content, information flows and further developments related to human security issues. The data reliability at various territorial levels of data collecting, processing and transmitting has been also analysed in this context. A special emphasis has been put on the actors involved in employing the environmental information for strategy and policy elaboration and implementation, management and administration as well as for scientific research, environmental education and public participation purposes. A typology of these actors from organisational viewpoint has been proposed and analysed, pointing out the need of enhancing the netwotking effects at both national and international level.
Keywords: 330